Hashing based Hybrid Online Voting Using Amazon Web Services - S, Murali; A, Manimaran; K, Selvakumar; Kumar S, Dinesh (International Journal of Engineering and Technology, 2018)
The secured web-based voting framework is the need of the present time. We propose another secure authentication for the online voting framework by utilizing face recognition and hashing algorithm. A simple verification process is accomplished during the initial registration process via email and phone. The voter is asked to give a unique identification number (UIN) provided by the election authority and face image at the time of main registration. This UIN is converted into a secret key using the SHA algorithm. The face image that is saved in the Amazon web service (AWS) acts as an authentication mechanism which enables people to cast their vote secretly. The voters, who cast numerous votes amid the way toward voting is guaranteed to be counteracted by encrypted UIN.Â  The election organizers can see the election parallelly as the voting is saved in the real-time database. The privacy of the voter is maintained as the details are converted into the key. In this system, an individual can vote from outside of his/her allocated constituency.Â Â